Peran Etika Profesi Memediasi Pengaruh Skeptisisme, Keahlian pada Ketepatan Pemberian Opini Auditor pada KAP Bali - Ristiana Dewi, Putu Ika; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 22 No 3 (2018), 2018)
The company's need for auditing of its corporate activities demonstrates the importance of auditing services (accountants) who are competent to assist in conducting the examination. An accountant in conducting the audit is required to pay attention to the accuracy of giving opinion. The purpose of this study is to analyze the role of professional ethics mediate the influence of professional skepticism of auditors and audit expertise on the accuracy of giving opinion by auditors at Public Accounting Firm in Bali. This research was conducted in all Public Accounting Firm in Bali as many as seven offices in Bali Region 2017 with auditor as much as 73 people. Using sample with saturated sample method. Data collection method was done by distributing questionnaires and data analysis techniques using path analysis technique. Based on the analysis result, professional skepticism of auditor and audit skill have positive effect on the accuracy of giving opinion of auditor at Public Accountant Office in Bali. Professional ethics is able to mediate the positive influence of auditor professional skepticism and audit expertise on the accuracy of providing auditor opinion on Public Accounting Firm in Bali. Keywords : Professional ethics, auditor professional skepticism, audit expertise, the accuracy of opinion giving